Effect of nicergoline on cerebral blood flow - Iliff, L. D. (1977)
Cerebral blood flow (CBF) was measured before and after intravenous injection of the cerebral vasodilator nicergoline in 13 patients with cerebrovascular disease. CBF increased in seven. The possibility that the effect of the drug in the remainder may have been masked by a fall of CBF which occurs during sequential measurement of patients at rest is discussed.